Katechizmy w Rzeczypospolitej od XVI do XVIII wieku: katechizm i jego produkcja - Pawlik, Wojciech (Źródła i monografie, 2010)
Zsfassung in engl. Sprache u.d.T.: Catechisms in the Polish Republic from the sixteenth to the seventeenth century : catechism and its production